2002
DOI: 10.1002/1521-3951(200201)229:2<803::aid-pssb803>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Interface Engineering in ZnO Epitaxy

Abstract: We report interface engineering in ZnO epitaxy to grow high-quality layers by plasma-assisted molecular beam epitaxy. Through interface engineering, we have succeeded in two-dimensional layer-by-layer growth of ZnO both on sapphire and GaN, and control of lattice polarity of ZnO films on a Ga-polar GaN template. MgO buffer has been used to convert the growth mode from a three-dimensional to a two-dimensional mode in ZnO epitaxy on sapphire. O-plasma pre-exposure on Ga-polar GaN templates has been employed to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…The improvement of the surface and the structural properties of the ZnO epilayer grown on Al 2 O 3 substrates utilizing ZnO buffer layers annealed in a vacuum might be attributed to the formation of the Zn-face ZnO buffers due to thermal treatment. The achievement Zn polarity of the surface in the ZnO buffer layer due to thermal annealing enhances the crystal quality of the ZnO films [18].…”
Section: Resultsmentioning
confidence: 71%
“…The improvement of the surface and the structural properties of the ZnO epilayer grown on Al 2 O 3 substrates utilizing ZnO buffer layers annealed in a vacuum might be attributed to the formation of the Zn-face ZnO buffers due to thermal treatment. The achievement Zn polarity of the surface in the ZnO buffer layer due to thermal annealing enhances the crystal quality of the ZnO films [18].…”
Section: Resultsmentioning
confidence: 71%
“…Many researchers used MgO buffer layers with success (eg. [10]). We undertook attempts to obtain planar ZnMgO layers using ZnO layer as a buffer because of a large structural misfit of MgO (cubic NaCl structure) and wurtzite ZnO.…”
Section: Nanostructures With a Zno Buffermentioning
confidence: 99%
“…14,15) Convergent beam electron diffraction (CBED), etching, coaxial impact collision ion scattering spectroscopy (CAICISS), and X-ray photoelectron spectroscopy (XPS) are widely used to determine the polarity of ZnO crystals. [16][17][18][19] However, Ullah et al reported that polarity inversion of ZnO films occurs during the growth of a thin nucleation layer. 20) Thus, a method for in situ monitoring during ZnO crystal growth is desired.…”
Section: Introductionmentioning
confidence: 99%